Kidney Involvement in PSTPIP1 Associated Inflammatory Diseases (PAID): A Case Report and Review of the Literature - Borgia, Paola; Papa, Riccardo; D'Alessandro, Matteo; Caorsi, Roberta; Piaggio, Giorgio; Angeletti, Andrea; Ceccherini, Isabella; Ghiggeri, Gian Marco; Gattorno, Marco (Frontiers in Medicine, 2021)
Pyogenic arthritis, pyoderma gangrenosum and acne (PAPA) syndrome, and the proline-serine-threonine phosphatase-interacting protein 1 (PSTPIP1)-associated myeloid-related proteinemia inflammatory (PAMI) syndrome are two distinct clinical conditions caused by heterozygous mutations of the PSTPIP1 gene. While skin and joint involvements are shared by both conditions, PAMI is characterized by hepatosplenomegaly, pancytopenia, and growth failure. Kidney involvement is exceptional in PSTPIP1-mediated disorders. The two missense PSTPIP1 variants associated with PAMI syndrome are p.E250K and p.E257K. Long-term treatment with interleukin (IL)-1 inhibitors is effective to control inflammatory manifestations and is usually well-tolerated. We report a case of a patient carrying the PSTPIP1 p.E250K mutation who developed a late-onset kidney involvement despite a long treatment with canakinumab and anakinra. Kidney biopsy showed focal segmental glomerulosclerosis that was treated with tacrolimus (0.1 mg/kg/day in two doses). A literature revision with the aim to assess the proportion and type of kidney involvement in PAMI syndrome revealed that heterogeneous nephropathies may be part of the clinical spectrum. Our study supports the importance of a periodic diagnostic work-up, including kidney laboratory tests and kidney biopsy, in individuals affected with PAMI syndrome. Kidney and liver functions may be impaired regardless of anti-cytokines treatments and additional therapy approaches (i.e., multi-drugs, hematopoietic stem cell transplantation) should be carefully considered.